ChemInform Abstract: Accessing Nitrosocarbonyl Compounds with Temporal and Spatial Control via the Photoredox Oxidation of N‐Substituted Hydroxylamines. Issue 40 (October 2015) - Frazier, Charles P.; Palmer, Leoni I.; Samoshin, Andrey V.; Read de Alaniz, Javier
Abstract Highly reactive acylnitroso species are generated from hydroxamic acids (I) via photoredox catalysis.